2005
DOI: 10.1111/j.1469-8137.2005.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental signals from leaves – a physiognomic analysis of European vegetation

Abstract: Summary• Leaf physiognomic traits vary predictably along climatic and environmental gradients. The relationships between leaf physiognomy and climate have been investigated on different continents, but so far an investigation based on European vegetation has been missing.• A grid data set (0.5 ° × 0.5 ° latitude/longitude) has been compiled in order to determine spatial patterns of leaf physiognomy across Europe. Based on distribution maps of native European hardwoods, synthetic chorologic flora lists were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 66 publications
3
104
0
Order By: Relevance
“…One of the aims of using these ordinal categories is to identify the distribution and potential environmental correlates of leaves at either end of the leaf shape continuum (broad→elongate). Traiser et al's (2005) categories may not do this effectively in the present study because they are based on European vegetation. For this reason, we also split the dataset based on the mean ratio of length to width for the sample.…”
Section: Quantifying Leaf Shapementioning
confidence: 99%
See 2 more Smart Citations
“…One of the aims of using these ordinal categories is to identify the distribution and potential environmental correlates of leaves at either end of the leaf shape continuum (broad→elongate). Traiser et al's (2005) categories may not do this effectively in the present study because they are based on European vegetation. For this reason, we also split the dataset based on the mean ratio of length to width for the sample.…”
Section: Quantifying Leaf Shapementioning
confidence: 99%
“…Our main source for exploring spatial variation in leaf shape across the Amazon rainforest is the RAINFOR database (Peacock et al, 2007 1 ), which has been constructed using information from 115 permanent plots distributed across eight South American countries, to which we added 26 data plots from Guyanas and Suriname compiled by the ATDN network (ter Steege et al, 2003). At the time of data extraction for this study (August 2006) the RAINFOR database contained 108 720 individual trees ≥10 cm DBH (diameter at breast height) from 3324 species.…”
Section: Database Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different traits have been explored for ecometric analyses. For plants, leaf shapes have been considered (Wolfe, 1995;Traiser et al, 2005). For animals, considered traits include teeth (Eronen et al, 2010a;Liu et al, 2012;Meloro and Kovarovic, 2013;Polly and Head, 2015;Fortelius et al, 2016;Zliobaite et al, 2016), limbs and locomotion (Polly and Head, 2015;Barr, 2017;Levering et al, 2017), skeletal traits (Lawing et al, 2012), as well as body mass (Meloro and Kovarovic, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in equatorial Africa, the proportion of untoothed margin species is positively correlated with wet months precipitation provided that precipitation is not less than 5 cm per month, while leaf size, particularly in mesophyll size, most strongly correlate with wet months and annual precipitation (Jacobs 1999). However, not all correlations between leaf physiognomy and precipitation are statistically significant, an observation that has been supported by a research from Europe: Traiser et al (2005) noticed that based on European vegetation data, none of these transfer functions can produce reliable precipitation prediction. Peppe et al (2011) studies data from 92 samples on a global scale, they found a low correlation between leaf size and MAP; even when the method of digital leaf physiognomy is used, this correlation increased only slightly.…”
mentioning
confidence: 95%